Perancangan Dan Implementasi Website Perpustakaan Digital Berbasis Web Menggunakan HTML, CSS, Javascript, Dan LocalStorage - Muh.Arfah Wahlil Pratama; Radika Fibrilya Herman; Anisa Fitri; Andi Umi Kalsum; Sardiansyah Sabir; Ahmad Dani; Andi Fajar Berlian; Firdha Musfidah; Nur Aziza (Jurnal Teknologi dan Bisnis Cerdas, 2026)
Libraries are one of the important facilities in supporting educational activities, research, and information dissemination. However, conventional library management still faces various challenges, such as inefficient record-keeping processes, difficulties in searching book data, and limitations in monitoring borrowing status. Therefore, a digital library system is needed to manage data in a computerized manner and provide easy access for users. This study aims to design and implement a web-based digital library website using HTML, CSS, and JavaScript by utilizing LocalStorage as the data storage medium. The developed system provides user authentication features (login and registration), book data management, book searching and sorting, book borrowing and returning, as well as real-time statistics on book availability. The system development process was carried out using the prototype method, which allows system adjustments based on user requirements. The implementation results indicate that the developed digital library website is able to improve the effectiveness of library data management and facilitate users in accessing book information and performing borrowing processes. With an interactive interface and a system that runs directly through a web browser without requiring a server-side database, this application is expected to serve as an alternative solution for managing small- to medium-scale libraries.